Biomass-derived carbon/silicon three-dimensional hierarchical nanostructure as anode material for lithium ion batteries. (December 2017) - Shen, Tong; Xie, Dong; Tang, Wangjia; Wang, Donghuang; Zhang, Xuqing; Xia, Xinhui.; Wang, Xiuli; Tu, Jinagping
Graphical abstract: A three-dimensional hierarchical silicon/carbon composite is synthesized by biomass-derived carbon and dopamine polymerization. The enhanced performance is attributed to the collaboration of thin carbon layer outside Si NPs and 3D conductive carbon framework. Highlights: The 3D conductive framework is fabricated from biomass-derived carbon. The enhanced performance is attributed to in-suit coating and 3D skeleton of carbon. The synthetic strategy is low-cost and environment friendly. Abstract: Three-dimensional hierarchical silicon/carbon nanostructure (3D AC-Si) is applied as the anode material for lithium-ion batteries (LIBs), where encapsulated Si NPs are uniformly bonded over interconnected carbon framework. The unique structure benefits from the binary functions of the naturally conductive network of biomass carbon and the in-suit carbon coating of dopamine. This 3D AC-Si composite behaves high specific capacity and good cycling stability (3353 mAh g −1 at a current density of 0.2 A g −1 ), as well as enhanced rate capability. Our findings exhibit a new strategy for preparing low-cost and environment friendly silicon/carbon composite and has potential to be extended to other anode materials for high-performance LIBs.